Hasan Chelik, The Translator Of Galaktion Tabidze’s Poetry - Dangadze, Natela (Yearbook of Kutaisi Ilia Chavchavadze Public Library, 2016)
The Thesis deals with the Turkish translations of the works of a great Georgian poet Galaktion Tabidze. It is said that generally making translations is a complicated psychological phenomenon and at the same time it is stipulated by subjective factor. By discussing different scientists’ point of views about the artistic translation, it reveals the huge importance and benefits of it. The thesis analyses Turkish translations of the poetry of Galaktion Tabidze’s “Azure-land, as a rose in rain-soaked sand” experimented by translator Hasan Chelik in different styles. If there is a literature, which is hard or easy to translate, the works of this poet can be easily referred to such kind of literature. It is very complicated for a translator to express quite original and symbolized forms and deciding the ultimate fate of translatable materials. Unexpectedness of artistic images, allusions, metaphors make the translation difficult. Translator has a huge responsibility, he/she should be well aware of not just the nature of materials he/she works on, but he/she should hold the virtue to conduct it in an artistic way. The translator has to reveal the inner rhythm of poetry and create its adequate version. Only such kind of work can be accepted by the reader and will be establish in its proper place. Introducing of prominent works of the famous Georgian poet Galaktion Tabidze to the rest of the world has a great importance in terms of culture dialogs. So, the scientific analysis of translations has a significant value.